2009
DOI: 10.1111/j.1365-2230.2008.03081.x
|View full text |Cite
|
Sign up to set email alerts
|

Hair removal with the long-pulse alexandrite and long-pulse Nd:YAG lasers is safe and well tolerated in children

Abstract: When administered appropriately, laser hair removal is safe and well tolerated in children aged < 16 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…The long-pulse 1,064-nm Nd:YAG laser has been widely used for removal of unwanted hair, 26,27 facial telangiectases, 28 and leg telangiectases 29,30 with minimal side effects. Recently, the clinical improvement of rhytides using long-pulse Nd:YAG laser application has also been demonstrated, 9 and a study of ultrastructural measurements suggested neocollagenesis after long-pulse 1,064-nm Nd:YAG laser treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The long-pulse 1,064-nm Nd:YAG laser has been widely used for removal of unwanted hair, 26,27 facial telangiectases, 28 and leg telangiectases 29,30 with minimal side effects. Recently, the clinical improvement of rhytides using long-pulse Nd:YAG laser application has also been demonstrated, 9 and a study of ultrastructural measurements suggested neocollagenesis after long-pulse 1,064-nm Nd:YAG laser treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For hypertrichosis, hair may be intermittently shaved. Hair removal lasers have not been studied well in nevus spilus, but recent studies have established the safety and efficacy of long‐pulse alexandrite and long‐pulsed Nd:YAG lasers in pediatric populations for other nevoid disorders such as nevoid hypertrichosis, CMN, and Becker’s nevus (15,16). Fitzpatrick skin types IV to VI are generally associated with a higher incidence of adverse side effects after laser hair removal because of melanin acting as the chromophore in the epidermis and in the follicle.…”
Section: Discussionmentioning
confidence: 99%
“…Children with excessive hair may experience severe psychological consequences . Depilatory methods include shaving, trimming, plucking, blanching, waxing, and laser .…”
Section: Discussionmentioning
confidence: 99%